Utilization of waste high density polyethylene (HDPE) as course aggregate replacement and glasses as filler in hot mix asphalt - Nurmazidah , Abdullah Zawawi (2015)
Flexible, rigid and composite are the three typical types of pavements. Commonly, flexible pavement is used especially in municipal, state and federal road in Malaysia. It consists five layers such as subgrade, subbase, base, base course and wearing course. In addition, the main structural function of pavement is to support the vehicles wheel load applied to the road 'and distribute to the. subgrade. High Density Polyethylene (HDPE) which is one of the polymers which is very familiar material used to produce many kind of product such as packing films, pipes and large blow and rotating moulding items while crushed glasses in non-metallic and inorganic material with 2.67 of specific gravity. Flexible pavement is commonly facing three major failures such as rutting, fatigue cracking and thermal cracking. The objective of this research is to investigate the optimum and effect usage of recycled HDPE as coarse aggregate replacement with crushed glasses as filler in modified asphalt mixture by determining the stiffness and permanent deformation. The modified asphalt mixture were produced from content concentrate of waste HDPE fillet range 2%, 4%, 6%, 8% and 10% of the weight of asphalt mixture with sieve size from 3.35 mm to 1.18mm and 4% to 6% is the range of the optimum bitumen content of hot mix asphalt wearing course 14 (ACWI4) with 80/100 of penetration grade of bitumen by referring Standard Specification for Road Works in Malaysia. The performance of the aggregate and bitumen is complying with Specification of Public Work Department 2008 in Malaysia. Therefore, these aggregates and bitumen can be used as asphalt for modified and unmodified sample. The Repeated Load Axial Test (RLAT), Indirect Tensile Stiffness Modulus Test (ITMS) were used to determine the permanent deformation and stiffness of asphalt, respectively. The densityvoid analysis indicates that the optimum bitumen content is 5.37% of weight of bitumen content. The result shows that the HDPE modified asphalt with crushed glass could enhance the stiffness of asphalt at 6% aggregate replacement at temperature 30°C. This modification also improves permanent deformation at 1800 cycles. Therefore the HDPE modified asphalt with crushed glasses is suitable to use for road pavement in term of economic and environmental aspects.